2020
DOI: 10.1177/1475921720929749
|View full text |Cite
|
Sign up to set email alerts
|

Acousto-ultrasonics-based health monitoring for nano-engineered composites using a dispersive graphene-networked sensing system

Abstract: Sensing is a fundamental yet crucial part of a functional structural health monitoring system. Substantial research has been invested in developing new sensing techniques to enhance sensing efficiency and accuracy. Practical applications of structural health monitoring approaches to real engineering structures require strict criteria for the sensing system (e.g. weight, position, intrusion and endurance), which challenge existing sensing techniques. The boom in nanotechnology has offered promising solutions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…The acousto‐ultrasonics‐based SHM where graphene nanoparticles are dispersed into a GF/epoxy composite to form a dispersive network sensing system was investigated. [ 256 ] A small area was required for a single detecting element to capture ultrasonic waves because of the dense graphene network formed inside the composite. The study concluded that the graphene sensor adds very negligible weight to the host structure and can provide rich information on the structural health status until the failure of the host structure.…”
Section: Applications Of Fiber Reinforced Smart Compositesmentioning
confidence: 99%
“…The acousto‐ultrasonics‐based SHM where graphene nanoparticles are dispersed into a GF/epoxy composite to form a dispersive network sensing system was investigated. [ 256 ] A small area was required for a single detecting element to capture ultrasonic waves because of the dense graphene network formed inside the composite. The study concluded that the graphene sensor adds very negligible weight to the host structure and can provide rich information on the structural health status until the failure of the host structure.…”
Section: Applications Of Fiber Reinforced Smart Compositesmentioning
confidence: 99%
“…Impact damage monitoring results showed that the first GFRP was more sensitive to matrix damage such as microcracks, while the second was more sensitive to delamination damage, which was because different locations of MWCNTs had different electrical responses to different forms of damage. Li et al 40,113 proposed a self-sensing functional GFRP, where a 2D graphene-formed percolating self-sensing network is Considering the agglomeration phenomenon when dispersing CNTs alone, as well as the excellent mechanical and electrical properties of CNT buckypaper, some scholars [114][115][116] have also used CNT buckypaper to develop self-sensing functional composite structures. Wang et al 116 designed and manufactured a type of self-sensing composite structure based on CNT buckypaper for in-suit SHM.…”
Section: Self-sensing Functional Composite Structuresmentioning
confidence: 99%
“…Impact damage monitoring results showed that the first GFRP was more sensitive to matrix damage such as microcracks, while the second was more sensitive to delamination damage, which was because different locations of MWCNTs had different electrical responses to different forms of damage. Li et al 40,113 proposed a self-sensing functional GFRP, where a 2D graphene-formed percolating self-sensing network is diffused in the GFRP, as shown in Figure 12(c). It can realize GW-based SHM without external installation of PZTs.
Figure 12. Different types of self-sensing functional composite structures based on doping or embedding method: (a) a self-sensing composite part with embed fiber sensors and tensile test results 111 ; (b) two kinds of self-sensing GFRPs and their impact monitoring results 112 ; and (c) self-sensing functional GFRP with diffuse graphene network and printed circuits.
…”
Section: Structural-sensing Integration Aircraft Smart Skinmentioning
confidence: 99%
“…Lamb wave based structural health monitoring (SHM) has received ever increasing attention [1][2][3][4]. Lamb wave has the ability to travel a long distance and is sensitive to multiple types of damage on the surfaces as well as inside of the platelike structures [3,5].…”
Section: Introductionmentioning
confidence: 99%